Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/ans.17675
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in surgical outcomes for low socioeconomic status patients in Australia

Abstract: Background: There are disparities in surgical outcomes for patients of low socioeconomic status globally, including in countries with universal healthcare systems. There is limited data on the impact of low socioeconomic status on surgical outcomes in Australia. This study examines surgical outcomes by both self-reported unemployment and neighbourhood level socioeconomic status in Australia. Methods: A retrospective administrative data review was conducted at a tertiary care centre over a 10-year period (2008)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…11,[22][23][24] Explanations for this include inadequate healthcare resources, poorer health literacy, and other social determinants of health. 25 Our study challenges the notion that socioeconomic status influences appendiceal perforation rates. This may be a testament to Australia's universal public healthcare (Medicare), which allows timely access to surgical care regardless of socioeconomic status.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…11,[22][23][24] Explanations for this include inadequate healthcare resources, poorer health literacy, and other social determinants of health. 25 Our study challenges the notion that socioeconomic status influences appendiceal perforation rates. This may be a testament to Australia's universal public healthcare (Medicare), which allows timely access to surgical care regardless of socioeconomic status.…”
Section: Discussioncontrasting
confidence: 54%
“…Indeed, the association between socioeconomic status and perforated appendicitis is most stark in countries such as the United States that do not have universal healthcare 11,22–24 . However, this does not account for the fact that low socioeconomic status adversely affects the outcomes of many other surgical pathologies that are also treated within Australia's healthcare system 25 . Another possible explanation is that our referral hospital has multiple systems in place to allow timely management of patients residing in low socioeconomic areas.…”
Section: Discussionmentioning
confidence: 99%
“…The contrasts between education categories were greatest toward the end of the study period, implying that the issue is current and requires further exploration. While the present dataset is inconclusive in terms of identifying underlying factors, it can be speculated that the widening mortality gradients are probably attributed to growing disparities in the domains already introduced above, i.e., access to care, severity of the condition at presentation, quality of care, and social determinants of health ( 29 ). For example, it has been suggested that access to care may have become more important for the early detection and complication-free treatment of conditions, or that management of conditions may have become more complex and advanced in ways that favor individuals with high socioeconomic status ( 32 ).…”
Section: Discussionmentioning
confidence: 80%
“…Speculative explanations can be offered. As previously proposed in the context of surgical procedures ( 29 ), the socioeconomic gradients in health outcomes are likely driven by disparities in access to care, severity of the condition at presentation, quality of the medical care itself, and social determinants of health. Since the selection of health care providers and procedures that are available to individuals differ markedly by socioeconomic position, the association with adverse event mortality may be mediated by the number and type of healthcare contacts.…”
Section: Discussionmentioning
confidence: 95%
“…However, on a much larger analysis of outcomes of coronary artery bypass surgery in U.S. veterans, Chandra et al 17 found homelessness to be an independent predictor of 30-day mortality. Within Australia, de Jager et al, 18 in their recent retrospective data review of surgical outcomes, identified a higher risk of postoperative mortality and surgical complication for unemployed and low socioeconomic background patients.…”
Section: Introductionmentioning
confidence: 99%